The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/md.0000000000022545
|View full text |Cite
|
Sign up to set email alerts
|

SUZYTM forceps facilitate nasogastric tube insertion under McGRATHTM MAC videolaryngoscopic guidance

Abstract: Background: Nasogastric tubes can be easily inserted in patients under general anesthesia. However, for difficult cases, insertion techniques that can be used in routine clinical practice are limited. SUZY forceps are designed for the removal of pharyngolaryngeal foreign bodies under guidance of a McGrath videolaryngoscope. We hypothesized that using SUZY forceps under McGrath videolaryngoscopic guidance may facilitate nasogastric tube insertion and tested this in a randomized controlled trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Contrastingly, the most severe mucosal injuries occurred in the posterior wall of the pharynx (RPW), compared to other regions in both the Smooth and Dif groups in the present study. Previous studies included patients undergoing general anesthesia in an operating room [ 11 , 12 ]. In contrast, the present study included patients with CPOA who were undergoing continuous CPR; thus, their necks may have been hyperextended, and passive neck movements during CPR might be involved in RPW mucosal injury [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrastingly, the most severe mucosal injuries occurred in the posterior wall of the pharynx (RPW), compared to other regions in both the Smooth and Dif groups in the present study. Previous studies included patients undergoing general anesthesia in an operating room [ 11 , 12 ]. In contrast, the present study included patients with CPOA who were undergoing continuous CPR; thus, their necks may have been hyperextended, and passive neck movements during CPR might be involved in RPW mucosal injury [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been proposed for the insertion of NGTs in patients who are intubated [ 16 , 20 ]. It has been reported that VLS-assisted NGT insertion is effective [ 12 , 18 , 21 ]. On the other hand, Nasr Isfahani and Nasri Nasrabadi [ 18 ] have recently reported that NGT insertion using two digital methods is less time-consuming and has a higher success rate, compared with VLS-assisted insertion in intubated patients at the ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In awake patients, the procedure is easy, as patients can cooperate by swallowing. On the contrary, in intubated patients, NG tube insertion can be di cult [20] . Ozer and Benumof [21] have reported that rst-attempt failure rates for blind insertion of an NG tube in an intubated patient can be as high as 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, in the present study, in both the Blind and Dif groups, the most severe mucosal injuries occurred in the posterior wall of the pharynx (oropharynx) compared to other regions. Previous studies had included patients undergoing general anaesthesia in an operating room [20,21] . In contrast, the present study included patients with CPOA who were undergoing continuous CPR.…”
Section: Discussionmentioning
confidence: 99%